Cancer In The Workplace: Rethinking Disability In Zimbabwe - Mahapa, Mildred (Advances in Social Sciences Research Journal, 2018)
The majority of people with cancer worldwide live in developing countries. These countries are facing a growing double burden of both infectious and non-communicable diseases such as cancer .Cancer has become a topical issue the world over as it is affecting the productive age group causing short or long term disability. It has affected the workplace environment and thus the need for research in this particular area. This literature review is aimed at examining the link between cancer and disability, the effects of cancer in the workplace as well as the strategies that can be adopted in managing employees with cancer. Hence, this paper will summarise research findings on the main challenges and barriers to meaningful employment for cancer patients. The analysis will also help inform future research in this area of work.